2021
DOI: 10.1021/acs.accounts.1c00069
|View full text |Cite
|
Sign up to set email alerts
|

Surface Fingerprinting of Faceted Metal Oxides and Porous Zeolite Catalysts by Probe-Assisted Solid-State NMR Approaches

Abstract: Metrics & MoreArticle Recommendations * sı Supporting Information CONSPECTUS: Acid catalysis in heterogeneous systems such as metal oxides and porous zeolites has been widely involved in various catalytic processes for chemical and petrochemical industries. In acid-catalyzed reactions, the performance (e.g., activity and selectivity) is closely associated with the acidic features of the catalysts, viz., type (Lewis vs Brønsted acidity), distribution (external vs internal surface), strength (strong vs weak), co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…For the second pathway, an adjacent carbon (C3, see Scheme 1a) loses one proton to the framework oxygen and forms a new double C2QC3 bond simultaneously. The combination of the last pathway with the protonation of the C1QC2 double bond is the positional isomerization of the double CQC bond, 12 which is confirmed by the H/D isotope tracer study in conjunction with 1 H NMR experiments 13,14 in the dehydration process of cyclohexanol in various zeolite pores. 15 Due to the lightest mass, hydrogen transfer is more feasible to achieve, which plays a significant role in the activation of reactants, transformation, and/or stabilization of intermediates toward products.…”
Section: Introductionmentioning
confidence: 60%
“…For the second pathway, an adjacent carbon (C3, see Scheme 1a) loses one proton to the framework oxygen and forms a new double C2QC3 bond simultaneously. The combination of the last pathway with the protonation of the C1QC2 double bond is the positional isomerization of the double CQC bond, 12 which is confirmed by the H/D isotope tracer study in conjunction with 1 H NMR experiments 13,14 in the dehydration process of cyclohexanol in various zeolite pores. 15 Due to the lightest mass, hydrogen transfer is more feasible to achieve, which plays a significant role in the activation of reactants, transformation, and/or stabilization of intermediates toward products.…”
Section: Introductionmentioning
confidence: 60%
“…Since the loss of BAS represented by the peak at 4.2 ppm is compensated by the generation of AlOH species not classified as traditional framework BAS species, both steaming samples show increases in the peak corresponding to non-BAS AlOH species located at 2.8 and 12–15 ppm in comparison with the fresh catalysts. The signal at 2.8 ppm is commonly attributed to AlOH species, with the corresponding 12–15 ppm peak attributed to framework/extra-framework interactions in both HZSM5 and HFER catalysts . Recently, the appearance of these two signals in the 1 H NMR spectra of HZSM5 catalysts has also been attributed to Al–OH species that are best described as partially coordinated framework species. ,,, However, these partially coordinated species can also be precursors to the generation of EFAl species after exposure to more severe conditions, which may then interact synergistically with existing framework sites through a variety of previously proposed mechanisms. , For the purpose of this analysis, the presence of these features is solely meant to indicate a qualitative increased presence of Al species that are not traditional framework sites upon high-temperature water treatment, a subset of which correlates to enhancements in activity for hexane cracking at elevated temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…4b ). Since a stronger adsorption for TMP gives rise to a more positive 31 P chemical shift, 16 it is reasonable to attribute the resonances at around −6, −14, −23 and −29 ppm to TMP adsorbed on the tin cations on (001), (101), (110), and (100) surfaces, respectively. It has also been shown that 31 P chemical shift exhibits a linear correlation with the adsorption energies.…”
Section: Resultsmentioning
confidence: 99%